Role of surgery in multifocal glioblastoma - Syeda Kubra Kishwar Jafri; Syed Sarmad Bukhari; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2022)
The management of multifocal glioblastomas is a point of constant discussion amongst neuro-oncologists. Best outcomes in glioblastoma management come from gross total resection (GTR) followed by concomitant radiation and chemotherapy (CCRT). Multifocal disease is resistant to GTR. Conventional management of these lesion is usually biopsy only followed by CCRT. Recent evidence has shown that there may be some benefit to attempting GTR of the largest lesion whenever safe to do so. Keywords: Glioblastoma multiforme; multifocal; radiotherapy; chemotherapy Continue...